Phytoremediation Methods and Reviews - Willey, Neil.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Phytoremediation: Methods and Reviews presents the most innovative recent methodological developments in phytoremediation research, and outlines a variety of the contexts in which phytoremediation has begun to be applied. A significant portion of this volume is devoted to groundbreaking methods for the production of plants that are able to degrade, take up, or tolerate the effects of pollutants. Phytoremediation: Methods and Reviews adopts a multidisciplinary approach to the examination of principles and practices of phytoremediation, from molecular manipulation to field application. Parts I and II discuss detailed protocols for achieving several different goals of phytoremediation, including enhancing contaminant degradation, uptake, and tolerance by plants; exploiting plant diversity for phytoremedation; modifying contaminant availability; and experimentally analyzing phytoremediation potential. Parts III and IV examine a variety of progressive techniques for phytoremediation and explore their implementation and success on a global scale. This cutting-edge volume highlights the myriad of contexts in which phytoremediation can be applied, and energizes new research by describing ways in which barriers to success have been recently overcome.
Manipulating Phenotypes and Exploiting Biodiversity -- Genetic Engineering of Plants for Phytoremediation of Polychlorinated Biphenyls -- Increasing Plant Tolerance to Metals in the Environment -- Using Quantitative Trait Loci Analysis to Select Plants for Altered Radionuclide Accumulation -- Detoxification of Soil Phenolic Pollutants by Plant Secretory Enzyme -- Using Real-Time Polymerase Chain Reaction to Quantify Gene Expression in Plants Exposed to Radioactivity -- Plant Phylogeny and the Remediation of Persistent Organic Pollutants -- Producing Mycorrhizal Inoculum for Phytoremediation -- Implementing Phytoremediation of Petroleum Hydrocarbons -- Uptake, Assimilation, and Novel Metabolism of Nitrogen Dioxide in Plants -- Manipulating Contaminant Availability and Developing Research Tools -- Testing the Manipulation of Soil Availability of Metals -- Testing Amendments for Increasing Soil Availability of Radionuclides -- Using Electrodics to Aid Mobilization of Lead in Soil -- Stable Isotope Methods for Estimating the Labile Metal Content of Soils -- In Vitro Hairy Root Cultures as a Tool for Phytoremediation Research -- Sectored Planters for Phytoremdiation Studies -- Phytoremediation With Living Aquatic Plants -- Near-Infrared Reflectance Spectroscopy -- Current Research Topics in Phytoremediation -- Using Hydroponic Bioreactors to Assess Phytoremediation Potential of Perchlorate -- Using Plant Phylogeny to Predict Detoxification of Triazine Herbicides -- Exploiting Plant Metabolism for the Phytoremediation of Organic Xenobiotics -- Searching for Genes Involved in Metal Tolerance, Uptake, and Transport -- Manipulating Soil Metal Availability Using EDTA and Low-Molecular-Weight Organic Acids -- Soils Contaminated With Radionuclides -- Assessing Plants for Phytoremediation of Arsenic-Contaminated Soils -- Contexts and Utilization of Phytoremediation -- Phytoremediation in China -- Phytoremediation in China -- Phytoremediation of Arsenic-Contaminated Soil in China -- Phytoremediation in Portugal -- Phytoremediation in Russia -- Phytoremediation in India -- Phytoremediation in New Zealand and Australia.
Keywords: Noise control; Biotechnology; Plant science; Botany; Environment; Noise Control; Biotechnology; Plant Sciences; Environment, general; Science, Humanities and Social Sciences, multidisciplinary